Prevalence of Parasitaemia, Anaemia and treatment outcomes of Malaria among School Children in a Rural Community in Ghana (Journal of Science and Technology, 2016)
A cross-sectional survey was conducted in the Ejisu-Juaben District to determine the prevalence of asymptomatic malaria and anaemia, and treatment outcomes in pupils of seven public schools public schools in a rural community in the forest belt of Ghana. Children with confirmed malaria parasites were randomly assigned to be treated with Artemisinin-based combination therapies available on the Ghanaian market. Post-treatment days 14 and 28 follow-up blood samples were taken to determine the treatment outcomes on peripheral parasitaemia and haemoglobin (Hb) concentrations. Out of 812 pupils (without malaria symptoms) who were screened, the baseline parasitaemia prevalence was 58.6%. Parasitaemia prevalence across the seven (7) public schools ranged from 49.7% to 71.0% (p =0.002). Post-treatment parasitaemia among the different treatment regimes were significant only at day 28 (p